Advanced Cardiac Life Support Checklists for Simulation-based Education - Diane Wayne; Matthew Nitzberg; Sangeetha Reddy; Rozanna Chester; Leonard Wade; Aashish Didwania; John Butter; Viva Siddall (Association of American Medical Colleges, 2014)
Abstract Introduction A decade ago, we received feedback from nurses at our institution that the performance of medical residents at advanced cardiac life support (ACLS) events varied. Some were very skilled and some needed assistance from other clinicians in order to lead a resuscitation event. Therefore, we began a simulation-based training course to supplement traditional ACLS education for internal medicine residents at Northwestern University. Over time, we received many requests for our simulation curriculum and checklists. We published them in MedEdPORTAL to share with the medical education community. This publication is an update of this curriculum/checklists to represent current medical practice and incorporate new American Heart Association (AHA) guidelines from 2010. Methods This curriculum consists of six ACLS scenarios using a high-fidelity patient simulator. A defibrillator, intubation equipment, bag-mask valve ventilation equipment, cardiac monitor, and syringes with ACLS medications are required. An instructor should be present during sessions for feedback and assessment. This can be any qualified ACLS instructor and does not need to be a physician. Assessment checklist scores should be carefully calibrated if more than one instructor is used to ensure that scoring is fair and reliable. We recommend that instructors are familiar with AHA guidelines and pilot test the curriculum before wide implementation. Results This curriculum had wide buy-in from the all involved. The residency program director is the senior author of this resource and ensured that all residents completed the program as part of their curriculum (participating in research was optional but completing simulation training was mandatory). From the first session, residents were the primary advocates for the program. Sessions were helpful, feedback was constructive, and skills were needed for clinical care. Residents asked for additional training in other skills leading to curricula for other procedures in subsequent academic years. Discussion This resource is effective for the six ACLS scenarios studied. It does not cover all ACLS events-just common ones seen at our institution. The assessment checklists cover many areas including patient care, medical knowledge, and communication skills (with patient and nurses), however, they are focused primarily on the team leader. Our tool does not evaluate team skills, but this should be developed in future work.